UNIX Operating System The Development Tutorial via UNIX Kernel Services - Liu, Yukun; Yue, Yong.; Guo, Liwei; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
"UNIX Operating System: The Development Tutorial via UNIX Kernel Services" introduces the hierarchical structure, principles, applications, kernel, shells, development, and management of the UNIX operation systems multi-dimensionally and systematically. It clarifies the natural bond between physical UNIX implementation and general operating system and software engineering theories, and presents self-explanatory illustrations for readers to visualize and understand the obscure relationships and intangible processes in UNIX operating system. This book is intended for engineers and researchers in the field of applicable computing and engineering modeling. Yukun Liu is an Associate Professor at the Department of Computer Science and Technology, Hebei University of Science and Technology, China; Professor Yong Yue is Director of the Institute for Research of Applicable Computing and Head of the Department of Computer Science and Technology, University of Bedfordshire, UK; Professor Liwei Guo is Dean of the College of Information Science and Engineering, Hebei University of Science and Technology, China.
Background and How to Start -- Editors -- Main Services of the UNIX Kernel -- UNIX Shells -- Internet and Computer Networking via UNIX.
Keywords: Computer science; Software engineering; Operating systems (Computers).; Computer software; Electronics; Computer Science; Operating Systems; Software Engineering/Programming and Operating Systems; Electronics and Microelectronics, Instrumentation; Algorithm Analysis and Problem Complexity